General Equilibrium Analysis of Regional Redistributive Effects of Investment for Reconstruction from the Great East Japan Earthquake - Kazunori Nakajima; Naoki Sakamoto (European Regional Science Association (ERSA), 2015)
By focusing on the impacts of investment in the disaster areas for reconstruction on the demand-side effects, the purpose of this study is to measure the economic impacts and regional spillover effects of investment for reconstruction. After the Great East Japan Earthquake of 2011, government investment in the disaster stricken areas was provided for reconstruction of capital stock damaged, and dynamic analysis is needed to reveal the long-term effects of investment. On the other hand, government investment for reconstruction results in increased aggregate demand, gross income, and gross production in the disaster areas, and has spillover effects on the other prefectures except for the disaster areas, even if the amount of damaged capital stock is given. This study develops a spatial computable general equilibrium (SCGE) model that consists of 47 prefectures and 20 industrial sectors in Japan. Also, this study assumes two scenarios. First, in order to measure economic damages in Japan, this study assumes a supply constraint by collapsed private capital stocks in the disaster areas (Iwate, Miyagi, Fukushima and Ibaraki). Second, in order to measure regional redistributive impacts of reconstruction investment, this study assumes that a reconstruction investment that evenly distributes funds to the disaster areas. The findings in this study are shown below. 1) By collapsed private capital stocks due to the earthquake, real GDP was estimated to decrease in 124 trillion dollars per year in total and to decrease in 120 trillion dollars per year in total in the disaster areas before the earthquake. Also, welfare was estimated to decrease in 109 trillion dollars per year in total and to decrease in 86 trillion dollars per year in total in the disaster areas. 2) After the earthquake, since investment for reconstruction improved real GDP and welfare in the disaster areas, this study showed that reconstruction investment contributed significantly to economic recovery in the disaster areas. By reconstruction investment, real GDP was estimated to increase in 1.6 trillion dollars per year in total and to increase in 56.7 trillion dollars per year in total in the disaster areas after the earthquake. Also, welfare was estimated to increase in 360 trillion dollars per year in total and to increase in 121 trillion dollars per year in total in the disaster areas. 3) Since investment for reconstruction resulted in welfare increase in 239 trillion dollars per year in total in regions except for the disaster areas, this study showed regional redistributive effect of reconstruction investment. The reason for this effect is that reconstruction investment in the disaster areas increases in demand in regions except for the disaster areas.
Keywords: C68; D58; D61; H54; 330; investment for reconstruction; the Great East Japan Earthquake; SCGE model